Environmental strategies and organizational competitiveness in the hotel industry: The role of learning and innovation as determinants of environmental success. (February 2015) - Fraj, Elena; Matute, Jorge; Melero, Iguácel
Abstract: This paper examines the links between proactive environmental strategies, organizational capabilities and competitiveness. A model is proposed and tested using a sample of 232 Spanish hotels. An orientation for learning and innovation are conceived not only as drivers for adopting pro-environmental policies, but also as determinants of competitiveness. Data are analyzed through the use of partial least squares. The findings confirm that a proactive environmental strategy and innovation favor organizational competitiveness. However, a learning orientation does not directly predict organizational competitiveness. The paper discusses both conceptual and practical implications for the development of successful hotel operations and management. Highlights: Learning oriented hotels are more likely to deploy a proactive environmental strategy. Innovative hotels are more proactive in their environmental strategies. Proactive environmental strategy positively affects organizational competitiveness. Innovative hotels perform better than non-innovative hotels. Learning orientation requires complementary capabilities to influence performance.